2015
DOI: 10.1007/s11244-015-0419-4
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Processes in Plasmonic Gold/TiO2 Photocatalysts Studied by Electron Paramagnetic Resonance

Abstract: X-band and W-band continuous-wave (CW) electron paramagnetic resonance (EPR) was used to study in situ light-induced (LI) mechanisms in commercial P90 titania (90 % anatase/10 % rutile) compared to plasmonenhanced Au-P90 photocatalyst. These materials were excited using UV and 532 nm visible light to generate different excitation states and distinguish pure charge separation from plasmon-assisted resonance processes. Up to nine different photoinduced species of trapped electrons and holes were identified. LI C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…We performed electron paramagnetic resonance (EPR) characterization ( Fig. 5c) and found that Cu/TNR is full of oxygen vacancies as evidenced by the appearance of Ti 3+ species 29,30 , while Ti 3+ species is not obvious for Cu/P25. The oxygen vacancy plays a key role in the adsorption and activation of polyols according to DFT calculations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We performed electron paramagnetic resonance (EPR) characterization ( Fig. 5c) and found that Cu/TNR is full of oxygen vacancies as evidenced by the appearance of Ti 3+ species 29,30 , while Ti 3+ species is not obvious for Cu/P25. The oxygen vacancy plays a key role in the adsorption and activation of polyols according to DFT calculations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ther ole of WO 3 in our catalyst can also be clarified by EPR measurements.D istinct from reduced Pt/TiO 2 -WO 3 , EPR signals from reduced Pt/TiO 2 were seen at g = 2.026, 2.017, and 2.014 ( Figure S13), which are assigned to O 2 À ,O 3 À , and O À ,respectively. [26] Compared with Pt/TiO 2 ,the exclusive oxygen intermediate (O 2 À )p roduced on the Pt/TiO 2 -WO 3 catalyst should be responsible for its high activity (Figure S14). Furthermore,asharp signal at g = 1.990 responsible for Ti 3+ in the anatase lattice appears over the reduced Pt/TiO 2 under light, 55 in parallel with the increase of the signal intensity of Ti 3+ in the rutile lattice.I nt his regard, it can be interpreted that excess photogenerated electrons induce the reduction of Ti 4+ in the Degussa P25 lattice.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Noble metals are one of the most extensively studied surface modifiers since they significantly inhibit the e − ∕h þ recombination under UV irradiation working as an electron sink, [19][20][21][22][23] and they can activate titania toward visible light irradiation due to localized surface plasmon resonance (LSPR), thus being so-called "plasmonic photocatalysts." [24][25][26] Although application of noble metals as an electron sink under UV irradiation was started almost 40 years ago, 19 the use of plasmonic properties for photocatalysis under visible light is quite new, 27 which means that opposite results have been published, e.g., on the mechanism [charge transfer (mainly electron, [27][28][29][30][31] but also simultaneous hole transfer has been reported 32 ), energy transfer, [33][34][35] and plasmonic heating [36][37][38] ] and on decisive factors for photocatalytic performance (size and shape of plasmonic NPs and properties of the support). [39][40][41][42][43][44] Despite contrary results, a common conclusion can be drawn, i.e., the morphology of photocatalysts (properties of metallic deposits, semiconductor, and interactions between them) is decisive for both photocatalytic activity and the mechanism.…”
mentioning
confidence: 99%